2021
DOI: 10.1001/jama.2021.9199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Ranitidine on Urinary Excretion ofN-Nitrosodimethylamine (NDMA)

Abstract: IMPORTANCE In 2019, the US Food and Drug Administration (FDA) received a citizen petition indicating that ranitidine contained the probable human carcinogen N-nitrosodimethylamine (NDMA). In addition, the petitioner proposed that ranitidine could convert to NDMA in humans; however, this was primarily based on a small clinical study that detected an increase in urinary excretion of NDMA after oral ranitidine consumption.OBJECTIVE To evaluate the 24-hour urinary excretion of NDMA after oral administration of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 27 publications
4
22
1
Order By: Relevance
“…Division of Applied Regulatory Science developed and published a mechanistic COVID-19 disease model that can be used to guide candidate drug selection and dosing strategies Division of applied regulatory science (DARS) designed a rigorous clinical study that carefully controlled for factors known to influence N-nitrosodimethylamine (NDMA) measurements including diet. The study found no evidence of increased NDMA content in participants' urine who were administered ranitidine (12).…”
Section: Optimizing Covid-19 Therapiescontrasting
confidence: 55%
See 2 more Smart Citations
“…Division of Applied Regulatory Science developed and published a mechanistic COVID-19 disease model that can be used to guide candidate drug selection and dosing strategies Division of applied regulatory science (DARS) designed a rigorous clinical study that carefully controlled for factors known to influence N-nitrosodimethylamine (NDMA) measurements including diet. The study found no evidence of increased NDMA content in participants' urine who were administered ranitidine (12).…”
Section: Optimizing Covid-19 Therapiescontrasting
confidence: 55%
“…Office of Pharmaceutical Quality, designed a rigorous clinical study that carefully controlled for factors known to influence NDMA exposure and measurements including diet (12). DARS developed and validated a sensitive analytical method that was used to measure NDMA in study participants' urine and blood.…”
Section: Over-the-counter Heartburn Medication Ranitidinementioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, NDMA has been recognized as a toxic agent widely found in multiple pharmaceuticals and fermented foods . NDMA is a strong carcinogen with a low acceptable daily limit of the US Food and Drug Administration (0.096 μg or 0.32 ppm per day) and potentially exposes millions of people to a risk of cancer . Therefore, there is a great need for a method for rapidly and sensitively detecting and quantifying NDMA.…”
Section: Resultsmentioning
confidence: 99%
“…56 NDMA is a strong carcinogen with a low acceptable daily limit of the US Food and Drug Administration (0.096 μg or 0.32 ppm per day) and potentially exposes millions of people to a risk of cancer. 57 Therefore, there is a great need for a method for rapidly and sensitively detecting and quantifying NDMA. Although chromatography/tandem mass spectrometry is a sensitive and reliable technique for ppb-level quantification, the operation process is particularly not suitable for highthroughput screening.…”
Section: ■ Results and Discussionmentioning
confidence: 99%